The Effort of Local Government to Develop Creative Economy of Embroidery Industry Sector for Supporting Regional Competitiveness Improvement (Study on Department of Industry and Trade of Pasuruan Regency) - Styawati, Ika Yuni (Jurnal Administrasi Publik, 2015)
Abstrak: Upaya Pemerintah Daerah dalam Membangun Ekonomi Kreatif di Sektor Industri Bordir dalam Mendukung Peningkatan Daya Saing Daerah (Studi pada Dinas Perindustrian dan Perdagangan Kabupaten Pasuruan). Ekonomi kreatif merupakan bagian dari gelombang ekonomi global di abad ke 21. Pemerintah menyadari bahwa ekonomi kreatif termasuk industri kreatif sangat potensial untuk dikembangkan guna mendukung peningkatan daya saing daerah. Pemerintah daerah kabupaten Pasuruan termasuk Dinas Perindustrian dan Perdagangan fokus pada pembangunan potensi ekonomi daerah termasuk industri bordir. DISPERINDAG memiliki beberapa strategi untuk mengembangkan industry bordir guna mendukung peningkatan daya saing daerah kabupaten Pasuruan. DISPERINDAG membangun kinerja industri bordir agar mampu berkontribusi terhadap perekonomian daerah, perdagangan domestik dan internasional serta dalam hal penyerapan tenaga kerja. Dalam mengembangkan industri bordir, DISPERINDAG berkoordinasi dengan ASPENDIR sebagai asosiasi pengusaha bordir. Kata Kunci: pembangunan, pemerintah daerah, ekonomi kreatif, industry kreatif, daya saing daerah Abstract: The Effort of Local Government to Develop Creative Economy of Embroidery Industry Sector for Supporting Regional Competitiveness Improvement (Study on Department of Industry and Trade of Pasuruan Regency). Creative economy is part of global economic wave in the 21st century. The government realize that creative economy include creative industry is potentially developed for supporting regional competitiveness improvement. Local government of Pasuruan Regency include Department of Industry and Trade concern to develop local economic potential includes embroidery industry. DISPERINDAG has several strategies to develop embroidery industry for supporting the improvement of regional competitiveness of Pasuruan Regency. DISPERINDAG develop the performance of embroidery industry in order to increase the contribution of regional economy, domestic and international trade and the contribution in absorbing the employee. In developing the embroidery industry, DISPERINDAG coordinate with ASPENDIR as the association of embroidery businessmen. Â  Keywords: development, local government, creative economy, creative industry, regional competitivenessÂ